P19. The brain's default mode is associated with executive oculomotor deficits in Parkinson's disease. Issue 8 (August 2015) - Gorges, M.; Müller, H.-P.; Ludolph, A.C.; Pinkhardt, E.; Kassubek, J.
<x xml:space="preserve">Abstract</x> Introduction Eye movements provide a valuable window into complex forms of human behavior. Impaired eye movement control in patients with Parkinson's disease (PD) has been consistently demonstrated besides the well-known motor symptoms (Pinkhardt and Kassubek, 2011). Saccadic intrusions are a common oculomotor manifestation in PD and interrupt smooth pursuit and fixation during tracking a 'jumping' target (visually guided reactive saccades) (Pinkhardt and Kassubek, 2011; Gorges et al., 2014). The default mode network (DMN) as observed with 'resting-state' functional MRI is crucially involved in higher cognitive processes such as attention (Buckner et al., 2008). We hypothesized that prevalence of saccadic intrusions in patients with PD reflects executive deficits which are closely associated with intrinsic functional connectivity (iFC) within the DMN. Methods The analysis was based on 31 patients with PD and 22 age-matched healthy controls. We acquired 'resting-state' functional MRI (3 Tesla; BOLD-sensitive T2∗-sequence) and video-oculographic recordings (VOG, Eye-Link I operating on 250 Hz sampling rate) of smooth pursuit eye movements and visually guided reactive saccades. 'Resting-state' functional MRI analysis followed standardized procedures (Gorges et al., 2014) with the DMN computed by seeding the posterior cingulate cortex (Buckner et al., 2008). The posterior cingulate cortex is known to be both a major node of the DMN (Buckner et al., 2008) and to play a critical role in eye movement control (Olson et al., 1996). Both smooth pursuit gain as a measure for saccadic intrusions and the saccadic intrusion rate during reactive saccades were analyzed in patients vs. controls and correlated with iFC within the DMN. Results VOG analysis revealed a significantly higher prevalence of saccadic intrusions during smooth pursuit (p < 0.001) and reactive saccades (p < 0.01) in PD patients compared with controls. Covariance analysis between the saccadic intrusion measures and the iFC in the DMN demonstrated significantly negative correlations (p < 0.001 for all clusters, corrected for multiple comparisons) in the sense that reduced iFC in almost all parts of the DMN was related to a higher prevalence of saccadic intrusions. Specifically, iFC between the posterior cingulate cortex and the (i) middle temporal lobe, (ii) thalamus, (iii) MST, (vi) precuneus (v), medial prefrontal cortex, and (vi) parietal lobule were significantly correlated with the saccadic intrusion rates. Conclusions A high prevalence of saccadic intrusions in patients with PD appears to be closely related to a lack of attention, pointing towards an increased distractibility that might be associated with the neuroimaging correlate of a disrupted DMN. This supports the hypothesis that impaired oculomotor control in PD reflects a behavioral correlate of disturbed higher functions rather than impaired oculomotor circuits in the brainstem.